2020
DOI: 10.1186/s13578-020-0380-1
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin and ubiquitin-like molecules in DNA double strand break repair

Abstract: Both environmental and endogenous factors induce various forms of DNA damage. DNA double strand break (DSB) is the most deleterious DNA lesion. The swift initiation of a complexed network of interconnected pathways to repair the DNA lesion is essential for cell survival. In the past years, the roles of ubiquitin and ubiquitin-like proteins in DNA damage response and DNA repair has been explored. These findings help us better understand the complicated mechanism of DSB signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 168 publications
(186 reference statements)
1
20
0
Order By: Relevance
“…Ubiquitination of proteins at DSB sites has been extensively studied and shown to play important roles in DSB response. These roles include promoting the recruitment of checkpoint and repair proteins at damage sites, altering protein–protein interactions, and clearing repair signaling ( 28 , 29 ). In this study, we observed K48-linked ubiquitination of Nbs1, which appeared to be responsible for premature disassembly of the MRN complex from DSB sites in RecQL4-defective cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination of proteins at DSB sites has been extensively studied and shown to play important roles in DSB response. These roles include promoting the recruitment of checkpoint and repair proteins at damage sites, altering protein–protein interactions, and clearing repair signaling ( 28 , 29 ). In this study, we observed K48-linked ubiquitination of Nbs1, which appeared to be responsible for premature disassembly of the MRN complex from DSB sites in RecQL4-defective cells.…”
Section: Discussionmentioning
confidence: 99%
“…The signal transduction inherent to the Early response to many DSBs is largely carried out by ataxia-telangiectasia mutated (ATM) protein kinase (see below, Figure 1C, and Savitsky et al, 1995;Ziv et al, 1997;Shiloh, 2003;Falck et al, 2005;Maréchal and Zou, 2013). At DSBs, ATM is the apical kinase, phosphorylating many substrates and triggering complex downstream post translational modifications (PTMs), including additional phosphorylation events, as well as methylation, ubiquitination (also known as ubiquitylation), neddylation, fatylation, ufmylation, and sumoylation of substrates (Matsuoka et al, 2007;Mu et al, 2007;Bensimon et al, 2010;Dou et al, 2011;Brown and Jackson, 2015;Yu et al, 2020).…”
Section: Introduction To Dna Damage Responsesmentioning
confidence: 99%
“…More recently, other ubiquitination-like modifications (e.g., sumoylation, acetylation, ISGylation, neddylation, palmitoylation, and UFMylation) have also been discovered. The roles of these posttranslational modifications (PTMs) in a myriad of cellular processes, such as receptor internalization (endocytosis), vesicle trafficking, immune response and inflammation, DNA damage response, autophagy, and cell death, have been greatly appreciated [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%